Influenza activity during the outbreak of coronavirus disease 2019 in Chinese mainland - Mi Liu; Lizong Deng; Dayan Wang; Taijiao Jiang (Biosafety and Health, 2020)
Since coronavirus disease 2019 (COVID-19) might circulate in the following seasons, it is essential to understand how COVID-19 influences other respiratory diseases, especially influenza. In this study, we analyzed the influenza activity from mid-November 2019 to March 2020 in Chinese mainland and found that the influenza season ended much earlier than previous seasons for all subtypes and lineages, which may have resulted from the circulation of COVID-19 and measures such as travel control and personal protection. These findings provide rudimentary knowledge of the co-circulation patterns of the two types of viruses.